Keadilan Upah dalam Perspektif Hadis: Analisis Praktik Ijarah pada Guru PPPK Paruh Waktu di Dinas Pendidikan Kabupaten Bantaeng - Yasir Arafat; Abdul Rahman Sakka; Muhammadiyah Amin (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
This study aims to analyze the wage practices of part-time PPPK teachers at the Department of Education in Bantaeng Regency from a hadith perspective, particularly concerning the principle of justice within the framework of Ijarah. The research employs a qualitative approach using field research combined with a thematic hadith analysis. Data were collected through interviews, observations, and documentation involving seven purposively selected informants and were analyzed using a descriptive-comparative method. The findings reveal that the wage system for part-time PPPK teachers has not been implemented optimally. Most informants have not received any wages since their appointment, while others receive very minimal compensation that is not proportional to their workload. Additionally, the study identifies the absence of clear employment contracts and prolonged delays in wage payments, which significantly affect teachers’ welfare and work motivation. From a hadith perspective, particularly the Prophet’s saying narrated by Ibn Majah regarding the obligation to pay wages before the worker’s sweat dries, it is emphasized that wages must be paid promptly, fairly, and proportionally. The comparison between empirical findings and hadith principles indicates a significant gap, suggesting that current wage practices are not fully aligned with the principles of justice in Islam. This study contributes to the development of thematic hadith studies by integrating normative and empirical approaches and provides practical implications for policymakers in designing a more just wage system for educators.